2016
DOI: 10.1364/oe.24.020586
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-broadband infrared metasurface absorber

Abstract: By using sub-wavelength resonators, metamaterial absorber shows great potential in many scientific and technical applications due to its perfect absorption characteristics. For most practical applications, the absorption bandwidth is one of the most important performance metrics. In this paper, we demonstrate the design of an ultra-broadband infrared absorber based on metasurface. Compared with the prior work [Opt. Express22(S7), A1713-A1724 (2014)], the proposed absorber shows more than twice the absorption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(84 citation statements)
references
References 30 publications
0
84
0
Order By: Relevance
“…We should note here that the applications of optical metasurfaces in the general sense of the word (i.e., patterned thin layers on a substrate) go beyond spatial wavefront manipulation. Thin light absorbers [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93], optical filters [94][95][96][97][98][99][100][101][102][103][104][105][106], nonlinear [107][108][109][110][111][112][113][114], and anapole metasurfaces [115,116] are a few examples of such elements. This review is focused on applications of metasurfaces in wavefront manipulation, and therefore it doesn't cover these other types of metasurfaces.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…We should note here that the applications of optical metasurfaces in the general sense of the word (i.e., patterned thin layers on a substrate) go beyond spatial wavefront manipulation. Thin light absorbers [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93], optical filters [94][95][96][97][98][99][100][101][102][103][104][105][106], nonlinear [107][108][109][110][111][112][113][114], and anapole metasurfaces [115,116] are a few examples of such elements. This review is focused on applications of metasurfaces in wavefront manipulation, and therefore it doesn't cover these other types of metasurfaces.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…A black body that absorbs broadband omnidirectional radiation is an ideal absorber, which has applications in energy harvesting, photodetectors, photothermal energy generation, and concealment . Film‐based absorbers, such as multiple pairs of stacked metal/dielectric films or multilayer‐stacked films, are suitable for the large‐area fabrication.…”
Section: Performance and Fabrication Characteristics Of The State‐of‐mentioning
confidence: 99%
“…Recent advances in this eld have witnessed the rapid development of the broadened absorption bandwidth (i.e., broadband PMAs) because broadband PMAs have both improved performance and increased capabilities. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Based on a range of literature reviews, we found that broadband PMAs can be obtained by employing two kinds of construction methods based on the unit structures of vertical stacking [11][12][13][14][15][16][17][18][19][20] or co-planar superlattices [21][22][23][24][25][26][27][28][29] consisting of several different dimensions of metallic elements. These two methods are not impeccable, however, and they suffer from some certain signicant disadvantages.…”
Section: Introductionmentioning
confidence: 99%